HUBUNGAN SELF EFFICACY DENGAN PEMILIHAN STUDI LANJUTAN PESERTA DIDIK KELAS IX DI SMPN 2 LUBUK SIKAPING - Anggun Laras Sukma; Besti Nora Dwi Putri; Yasrial Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe self-efficacy, further study choice, and the relationship between self-efficacy and further study choice among ninth-grade students at SMPN 2 Lubuk Sikaping, Pasaman Regency. The study employed a quantitative approach with a correlational method. The sample consisted of 95 students selected through proportional sampling. Data were collected using self-efficacy and further study choice questionnaires and analyzed using percentage analysis and correlation tests. The results indicate that students’ self-efficacy was in the high category, while their further study choice was in the low category. The correlation analysis revealed a positive and significant relationship between self-efficacy and further study choice, with a moderate level of correlation and a significance value of 0.000. These findings suggest that self-efficacy plays an important role in students’ ability to determine further study choices.